2013
DOI: 10.1111/idh.12038
|View full text |Cite
|
Sign up to set email alerts
|

Senior dentists' perceptions of dental therapists' roles and education needs in Malaysia

Abstract: This study suggests that Malaysian SDOs have positive perceptions of the current roles of DT and of the expansion of some of their clinical tasks to include broader client groups through further training and education. These findings indicate a need to revise the current curriculum and legislation pertaining to DT's education and scope of practice in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The respondents in the present study were also not satisfied with their career opportunities. This echoed the findings of a previous local survey (19) and indicated the commitment of dental therapists to continuing education and personal development. In terms of career opportunities, Malaysian dental therapists have limited opportunities to attain higher academic qualifications up to degree level as compared to other countries.…”
Section: Roles Of Dental Therapistsupporting
confidence: 80%
See 2 more Smart Citations
“…The respondents in the present study were also not satisfied with their career opportunities. This echoed the findings of a previous local survey (19) and indicated the commitment of dental therapists to continuing education and personal development. In terms of career opportunities, Malaysian dental therapists have limited opportunities to attain higher academic qualifications up to degree level as compared to other countries.…”
Section: Roles Of Dental Therapistsupporting
confidence: 80%
“…Part D consisted of 34 items on their current and future roles (divided into four categories namely their clinical skills, oral health promotion activities, administration work and the aspects of the dental team where they are located). Details of Part D of the questionnaire have been described elsewhere .…”
Section: Study Population and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, issues around UDAs and payment for DTs time were deciding factors. Internationally, attitudes towards the DTs’ role were noted to influence the amount and type of work referred to them in practice . USA‐based literature found that the more tasks delegated to DTs, the more patients were seen in practice, and there was higher productivity …”
Section: Discussionmentioning
confidence: 99%
“…Internationally, attitudes towards the DTs' role were noted to influence the amount and type of work referred to them in practice. [69][70][71] USA-based literature found that the more tasks delegated to DTs, the more patients were seen in practice, 57 and there was higher productivity. 72 The literature and case studies that we have presented here both reported that carrying out a variety of tasks and feeling valued by the dentist lead to increased DT job satisfaction.…”
Section: Directmentioning
confidence: 99%